Pengaruh Penilaian Kinerja, Keterampilan Kerja, dan Kualitas Kehidupan Kerja Terhadap Kinerja Karyawan - Woro Sulistyorini; Sutianingsih (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This research explores the effects of performance appraisals, job competencies, and work-life quality on employee output. The author adopts an associative research methodology, drawing upon primary data. Questionnaires were distributed to 203 staff members at Pandan Arang Hospital in Boyolali to collect data. This study utilizes saturated sampling; consequently, the entire population was included. Data analysis proceeded in three key stages: outer model assessment, inner model evaluation, and hypothesis testing performed with PLS version 3 software. This study indicates: 1) a strong link between performance evaluation and employee performance. 2) a strong link between job skills and employee performance, 3) a strong link between performance quality of work life and employee performance.